2017
DOI: 10.1021/jacs.7b03850
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Separation of Acetylene from Carbon Dioxide and Ethylene in a Microporous Material

Abstract: Selective separation of acetylene (CH) from carbon dioxide (CO) or ethylene (CH) needs specific porous materials whose pores can realize sieving effects while pore surfaces can differentiate their recognitions for these molecules of similar molecular sizes and physical properties. We report a microporous material [Zn(dps)(SiF)] (UTSA-300, dps = 4,4'-dipyridylsulfide) with two-dimensional channels of about 3.3 Å, well-matched for the molecular sizes of CH. After activation, the network was transformed to its cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
408
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 466 publications
(435 citation statements)
references
References 48 publications
27
408
0
Order By: Relevance
“…[21] It is intriguing to find that CPM-107op can take up 136.7 cm 3 g À1 and 97.5 cm 3 g À1 of C 2 H 2 at 273 Ka nd 298 K( Figure S21), respectively.The uptake capacity at 298 Kishigher than some benchmark C 2 H 2 /CO 2 -separation materials such as UTSA-300 (67 cm 3 g À1 )and HOF-3 (47 cm 3 g À1 ). [22] Theisosteric heat for C 2 H 2 adsorption is also calculated to be in the range of 32-37 kJ mmol À1 ,a pparently larger than that of CO 2 (Figure 4). To evaluate the potential separation capability of CPM-107op,the ideal adsorbed solution theory (IAST) is applied to calculate the selectivity of C 2 H 2 /CO 2 in the equal mixture at 298 K (Figure S22, S23).…”
Section: Angewandte Chemiementioning
confidence: 94%
“…[21] It is intriguing to find that CPM-107op can take up 136.7 cm 3 g À1 and 97.5 cm 3 g À1 of C 2 H 2 at 273 Ka nd 298 K( Figure S21), respectively.The uptake capacity at 298 Kishigher than some benchmark C 2 H 2 /CO 2 -separation materials such as UTSA-300 (67 cm 3 g À1 )and HOF-3 (47 cm 3 g À1 ). [22] Theisosteric heat for C 2 H 2 adsorption is also calculated to be in the range of 32-37 kJ mmol À1 ,a pparently larger than that of CO 2 (Figure 4). To evaluate the potential separation capability of CPM-107op,the ideal adsorbed solution theory (IAST) is applied to calculate the selectivity of C 2 H 2 /CO 2 in the equal mixture at 298 K (Figure S22, S23).…”
Section: Angewandte Chemiementioning
confidence: 94%
“…Supramolecular cages with asimilar binding effect in solution have been reported before; [5] however,i ti sc hallenging to develop porous solid materials to mimic such an induced-fit behavior for molecular recognition, which would be desired for many large-volume applications including industrial gas purification.Acetylene (C 2 H 2 )i sa ni mportant starting material for many chemical [6] and electronic [7] products.Y et, it is very reactive and may cause unwanted chemical reactions.S team cracking of hydrocarbons is the primary method for producing lighter alkenes and C 2 H 2 is an inevitable byproduct. [8] Recent studies have revealed that anumber of metal-organic frameworks [9] (MOFs) show an increased C 2 H 2 selectivity over other gas molecules through ligand functionalization, [10] pore size/shape customization, [11] surface polarization, [12] and, in particular, open-metal-sites incorporation. [13] Thel atter usually contributes more to the binding affinity because of the ability of C 2 H 2 to coordinate to the metal center.H owever, most of the MOF materials studied for C 2 H 2 selectivity have rigid frameworks whose dimensions barely change upon C 2 H 2 loading, which inevitably results in ad ecrease in binding affinity once the strongest adsorption sites for C 2 H 2 are occupied.To mimic an enzyme-like behavior,flexible MOFs whose scaffolds can self-adapt to match the size of the guest molecules are of particular interest.…”
mentioning
confidence: 99%
“…The C 2 H 2 /C 2 H 4 adsorption selectivity of PAF-120 also outmatches those of somet ypical MOFs under the same conditions, such as Fe-MOF-74 (selectivity:1 .87), [9] M'MOF-2a (selectivity: 1.93), [52] and NOTT-300 (selectivity:2 .3), [10] but is outperformed by the selectivities of porousa dsorbents such as JCM-1 (selectivity:1 3.2), [16] SIFSIX-2-Cu-i (selectivity:4 1.01), [2] and UTSA-300a (selectivity > 10 4 ). [11]…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] Some MOFs have been documented to be energy-efficient and environmentally friendly adsorbentsc apable of C 2 H 2 /C 2 H 4 and CO 2 /N 2 separation. [1,2,4,[7][8][9][10][11][12][13][14][15][16] Porous organic frameworks (POFs) or covalent organic frameworks (COFs), [17][18][19][20][21][22][23][24] an emerging family of porous materials, have attracted interest from the scientific communityf or their potentiali nm olecular separation, [25,26] catalysis, [27][28][29] drug delivery, [30,31] energy storage, [32][33][34][35] and many other applications. [36][37][38][39][40][41] In 2005, in pioneering work, crystalline COF-1 and COF-5 were fabricated b...…”
Section: Introductionmentioning
confidence: 99%